Spatial Characteristics of Labor Mobility and Innovation inside an Industrial Cluster: Some Reflections from Siteler in Ankara - Burak Beyhan (European Regional Science Association (ERSA), 2010)
Although the literature on industrial clusters and districts emphasizes the role of labor mobility in the diffusion of innovation and tacit knowledge, relatively little academic effort supported by strong empirical evidences has been made in order to reveal the association between labor mobility and innovation in an appealing way. Likewise, the experimental studies outlining the spatial characteristics of labor mobility and innovation inside a cluster are nearly absent. In terms of its inner spatial configuration, the cluster itself is a black box for not only economists but also for geographers and planners especially when the interplay of labor mobility and innovation is considered. Most of the studies either tend to concentrate on a single cluster without informing us about the actual relevance of space inside the cluster or compare the clusters in a region (or country) again without developing a proper measure for the comparisons of the respective clusters in terms of the spatial characteristics of the labor mobility and innovation inside them. In this regard, the basic pursuit of this paper is both to develop and utilize simple measures in order to account for the relevance of space in different configurations of innovation and labor mobility inside an industrial cluster by making use of the parameters and analysis developed for Social Network Analysis (SNA), Space Syntax (SS) and Geographic Information Systems (GIS). What is especially remarkable in this study is the preference for free and open source software and establishment of author's own algorithms. In an attempt to reveal the spatial contexts of the labor mobility and innovation occurring inside a cluster, firstly streets involved in Siteler, an industrial cluster in Ankara and specialized in furniture production, are divided into segments according to some intuitive criteria. Subsequently, a series of analysis is conducted by employing parameters of SNA, SS and GIS. What is evident from this paper is that labor mobility and innovation inside Siteler is strongly imprinted with the spatial configuration of streets in the cluster.
Keywords: 330